Plan estratégico de marketing para el posicionamiento de la empresa “frobun” de la parroquia Mulaló del cantón Latacunga provincia de Cotopaxi para el período 2014-2017 - Calala Rocha, María Fernanda (2015)
This research work has as objective to contribute to the improvement of the company in terms of competitiveness, productivity and increased revenue through the development of a strategic marketing plan; whose results will be reflected in the profitability of the entity; the essential problem is framed in the low position that the same has within the market as a result of poor implementation of marketing strategies within the environment in which it develops; For this reason the diagnosis of the company is essential to identify weaknesses, Strength, Threat and opportunities that will help to determine the actions to do ….